Physical Activity to Reduce Fatigue in Rheumatoid Arthritis: A Randomized Controlled Trial. Issue 1 (6th December 2017) - Katz, Patricia; Margaretten, Mary; Gregorich, Steven; Trupin, Laura
Abstract : Objective: Effective treatments for rheumatoid arthritis (RA) fatigue are limited. We tested the effect of a pedometer‐based intervention on increasing physical activity and decreasing fatigue among individuals with RA. Methods: Participants completed baseline questionnaires; had 1 week of activity monitoring; were randomized to control (education [EDUC]), pedometer and step‐monitoring diary (PED), or pedometer and diary plus step targets (PED+) groups, and were followed for 21 weeks. At week 10, questionnaires were administered by phone to all participants. During the final week, all participants again had 1 week of activity monitoring. Primary outcomes were changes in average weekly steps and fatigue (Patient‐Reported Outcomes Measurement Information System 7‐item questionnaire) from baseline to week 21. Secondary outcomes were self‐reported disease activity, physical function, pain interference, and depressive symptoms. Changes in steps were tested using a linear mixed model. Changes in fatigue were tested with repeated‐measures models, including baseline, week‐10, and week‐21 scores. Results: A total of 96 individuals participated. Eight did not complete the 21‐week assessments. Both intervention groups significantly increased steps (+1, 441 [ P = 0.004] for PED and +1, 656 [ P = 0.001] for PED+), and the EDUC group decreased steps (‐747 [ P = 0.14]) (group‐by‐time interaction P = 0.0025). Between‐group changes in fatigue were not significantly different (interaction P = 0.21). Mean changes in fatigue scores from baseline to week 21 were ‐1.6 (with‐group P = 0.26), ‐3.2 ( P = 0.02), and ‐4.8 ( P = 0.0002) for EDUC, PED, and PED+ groups, respectively. Function and self‐reported disease activity also improved in the PED and PED+ groups. Conclusion: Provision of pedometers, with and without providing step targets, was successful in increasing activity levels and decreasing fatigue in this sample of individuals with RA.